Pengaruh Faktor Sosial Demografi Terhadap Curahan Jam Kerja Pekerja Perempuan Pada Keluarga Miskin Di Desa Pemecutan Kaja Kecamatan Denpasar Utara - Budiantari, Ni Nyoman Sri; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 11, November 2013 (pp. 492-546), 2013)
Important generalizations about poverty is more poverty suffered by women. Working women have reasons to support their families due to the uncertain economic conditions which resulted in disruption of family economic stability. The purpose of this study was to determine the effect of age, education and family income to the outpouring of working hours of women workers in poor families. The research was conducted in the village of Pemecutan Kaja, Denpasar District Utara. The study sample size was calculated by as many as 73 people Proportionate Stratified Random Sampling method. The analysis technique used is multiple linear regression analysis. Simultaneously known that age, education and family income significantly influence the flow of working hours of women workers in poor families. Partially, the results of this study indicate that the factors of age and family income negatively affect the flow of working hours of female workers age factor is a positive influence on the outpouring of working hours of women workers. Advice obtained from this study are: (1) North Denpasar district work program is expected to align with the city government to pay more attention to health care, education and help provide venture capital to the poor, (2) regional government in order to monitor and review the entire district the program is executed.
Keywords: Age; Education; Family Income; Hours Expended Women